Landscape Design Methodology: Pattern formation through the use of Cellular Automata - Sergi Abellán Sanfélix; Marcel Bilurbina Camps; Marilena Christodoulou (Temes de Disseny)
The purpose of this study is to develop a landscape design methodology based on the use of a Cellular Automaton (CA) algorithm in order to introduce the plant-plant interaction factor in the plantating design of a site. This design methodology introduces the relationships between neighboring individuals of different species as parameters for the project. These parameters are codified in order to define the Cellular Automaton rules. Parameters related to the growth and morphologic characteristics of the species as well as programmatic and aesthetic parameters of the project may be introduced as rules that influence the behavior of the CA algorithm.